Effect of height intensity intermittent-training (HIIT) and plyometric training to reponses of immunological system to soccer players. - ROUABI, Sifeddine; Fethi , YOUSFI (sports creativity, 2025)
Our study aimed to compare two methods of muscle power training (HIIT, polymeric training) about the effect that these two methods can affect the individual's immune system. A sample of 12 players was selected to JSKA club football in the 2018/2019 season .Results: the Polymeric training affects the numbers (lymphocytes and monocytes) with a statistically significant decrease and a greater degree of HIIT due to the use of microscopic lacerations and infections from HIIT. - Plyometric training and HIIT affect the numbers of nitrophil with a statistically high but more when applying HIIT, this is to increase the number of nitrophil